Global surgical and anaesthetic task shifting: a systematic literature review and survey. (27th April 2015) - Federspiel, Frederik; Mukhopadhyay, Swagoto; Milsom, Penelope; Scott, John W; Riesel, Johanna N; Meara, John G
Abstract: Background: Billions of people worldwide lack access to surgical care; this is in part driven by severe shortages in the global surgical workforce. Task shifting, the movement of tasks to associate clinicians or non-specialist physicians, is a commonly implemented yet often contentious strategy to expand the surgical workforce. A more complete understanding of the global distribution and use of surgical and anaesthetic task shifting is needed to strengthen strategic planning efforts to bridge the gap between surgical and anaesthetic providers. We aimed to document the use of task shifting worldwide with an in-depth review of the literature and subsequent confirmation of practices through a provider survey. Methods: We did a literature search according to PRISMA guidelines. We searched PubMed, Embase, The Cochrane Library, CINAHL, WHOLIS, and five regional databases for journal articles published between Jan 1, 1995, and Aug 29, 2014, for titles or abstracts mentioning surgical or anaesthetic care provision by associate clinicians or non-specialist physicians. We also searched article references and online resources. We extracted data for health cadres performing task shifting, the types of tasks performed, training programmes, and supervision of those performing tasks and compared these across regions and income groups. Additionally, we then undertook an unvalidated survey to investigate the use of task shifting at the country level, which was sent to surgeons and anaesthetists in 19 countries across all major regions of the world. Findings: We identified 62 studies. The review and survey provided data for 163 and 51 countries respectively, totalling 174 countries. Surgical task shifting occured in 30 (33%) of 92 countries. Anaesthetic task shifting occured in 108 (65%) of 165 countries. Task shifting was documented across all World Bank income groups. Where relevant data were available, in high-income countries, associate clinicians were commonly supervised (100% [four countries] for surgery and 90% [20 countries] for anaesthesia). In low-income countries, associate clinicians undertook surgical and anaesthetic procedures without supervision (100% for surgery [five countries] and 100% for anaesthesia [22 countries]). Interpretation: Task shifting is used to augment the global surgical workforce across all geographical regions and income groups. Associate clinicians are ubiquitous among the global surgical workforce and should be considered in plans to scale up the surgical workforce in countries with workforce shortages. Reporting bias is likely to have favoured the more novel and successful task shifting initiatives, which could have caused our results to underestimate the absolute number of countries that use task shifting. Although surgical and anaesthetic task shifting has been described in many countries, further research is required to assess outcomes, especially in low-income and middle-income countries where supervision is less robust. Funding: None.